Impact of climate and human-induced fire on the Dongyuan Lake, Southern Taiwan during the last 1850 cal years BP - Abdur Rahman; Liang-Chi Wang; Neng-Ti Yu; Jiun-Yee Yen (Geoscience Letters)
Abstract This study investigates the relationship among the wildfires, climate, and humans and their combined impact on the Dongyuan Lake in southern Taiwan using a sediment core that covered the last 1850 cal years BP. Charcoal accumulation rate (CHAR) peaks, low total organic carbon (TOC), total nitrogen (TN), TOC/TN ratios, and carbon isotopic composition (δ13Corg), combined with low sedimentation rate (SR) and silt dominance suggested a loss of organic carbon, no or low runoff and soil instability due to wildfires during 1850–1700, 1600–1450, and 1350–1100 cal years BP. This led to silt dominance, further indicating drier climatic conditions. Two intermittent wet phases during 1700–1600 and 1450–1350 cal years BP, indicated by high TOC, TN, TOC/TN ratios, and δ13Corg, suggested peatland formation. After 1100 cal years BP, increased runoff, and organic matter accumulation indicated peatification, suggesting wetter conditions characterized by higher TOC, TN, TOC/TN ratios, δ13Corg, and SR. Wetter periods continued, but the appearance of diatoms indicated shallow water levels during 750–500 cal years BP and from 350 cal years BP to the present. CHAR peaks suggest wildfire activity, and combined with archaeological evidence, this implies human-induced burning during these periods. The variation in pH and nutrient dynamics (indicated by PCA analysis of diatoms) were closely linked to wildfire intensity and frequency. Infrequent wildfires (750–500 cal years BP) caused lake acidification, while frequent fires (350 cal years BP to present) raised pH. In the past 150 years, human activities, mainly deforestation and acid rain, have contributed to lake acidification.